2019
DOI: 10.1097/md.0000000000016890
|View full text |Cite
|
Sign up to set email alerts
|

Survey of job burnout and depression in standardized residency training programs in China

Abstract: To evaluate job burnout and its impacts on mental health among clinical residents in a 3-year standardized residency training program in China.This cross-sectional study was conducted among all residents in the Department of Internal Medicine of the Peking Union Medical College Hospital in August 2017. Job burnout and depressive symptoms were assessed using the Maslach Burnout Inventory-General Survey and the Center for Epidemiological Survey, Depression, respectively.Among the 159 residents who completed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…On the one hand, not only has the patient-physician relationship remained poor but the patients' distrust of the current healthcare system and policies is also increasing, and the number of violent incidents against healthcare providers are increasing each year (The Lancet, 2014). On the other hand, because of the huge workload, the proportion of residents experiencing burnout syndrome in China is as high as 61-71% (Li et al, 2020;Huang et al, 2020;Zhang et al, 2019). In addition, as SRTP in China was initiated nationally, residents face increased challenges, such as three years of highstress training, career uncertainty, and low salary.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, not only has the patient-physician relationship remained poor but the patients' distrust of the current healthcare system and policies is also increasing, and the number of violent incidents against healthcare providers are increasing each year (The Lancet, 2014). On the other hand, because of the huge workload, the proportion of residents experiencing burnout syndrome in China is as high as 61-71% (Li et al, 2020;Huang et al, 2020;Zhang et al, 2019). In addition, as SRTP in China was initiated nationally, residents face increased challenges, such as three years of highstress training, career uncertainty, and low salary.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because insufficient sleep reduces work efficiency, resulting in reduced sense of satisfaction and achievement [ 43 , 44 ]. Dental postgraduates with children had a lower risk of job burnout, probably because children bring happiness to parents [ 45 ]. Having children has been shown to mitigate psychological burnout [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Depressive symptoms and career choice regret were risk factors for job burnout. Previous studies have shown that symptoms and related factors for job burnout and depression exhibit obvious overlaps [ 26 , 45 ]. We established that job burnout is strongly associated with career and specialty choice regret, consistent with previous studies [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Especially, residents in the SRTP could be most vulnerable to anxiety and depression, because they may not be capable of heavy workloads, the morbidity and mortality of patients, pressure of patient and service demands, and challenging daily work routines [ 15 ]. A previous study has shown that the rate of depression was 28.3% among residents in the SRTP [ 16 ]. Given that mental health can have a detrimental impact on residents in the SRTP and health services, including quality of patient care and medical errors, research needs to identify the mechanism between social support, emotional exhaustion, and depression/anxiety to inform effective interventions.…”
Section: Introductionmentioning
confidence: 99%